A Pilot Randomized Controlled Trial Using Prophylactic Dressings to Minimize Sacral Pressure Injuries in High-Risk Hospitalized Patients. (August 2017) - Walker, Rachel; Huxley, Leisa; Juttner, Melanie; Burmeister, Elizabeth; Scott, Justin; Aitken, Leanne M.
This pilot randomized controlled trial examined the effect of prophylactic dressings to minimize sacral pressure injuries (PIs) in high-risk hospitalized patients and assessed feasibility criteria to inform a larger study. Eighty patients were recruited at admission points (the emergency department and surgical care unit) or directly from participating wards in the general medical-surgical setting following the assessment of high risk of sacral PI. Participants were randomized into either the routine care or routine care and silicone foam border dressing group. Outcome assessment comprised digital photographs of each participant's sacrum every 72 hr for evaluation by a blind-to-intervention assessor. Sixty-seven participants had at least one sacral photograph taken and assessed by a blind-to-intervention assessor. Three participants were assessed as having a Stage I PI. Although the use of photography was effective, feasibility criteria identified challenges related to bias, blinding, weight assessment, preparation of nursing staff, and sample size estimation.